PENGUJIAN OVERREACTION HYPOTHESIS DI BURSA EFEK INDONESIA PADA PERIODE BULLISH DAN PERIODE BEARISH - Fazry Sidiq (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Khairun, 2014)
This study aims to obtain empirical evidence about the excessive reaction (overreaction) is indicated by the change in the stock price by using the returns of the securities in question . This reaction can be measured by abnormal returns earned by the securities to investors . Previous research found a proven loser portfolio outperformed the winner portfolio , but the portfolio winner does not have a tendency to be a loser .This research is a quantitative - deductive hypotheses through by developing theories that already exist . The core of this research is to observe the reaction of investors over the possibility of the existence of the overreaction effect by looking at the variable weekly abnormal return in 2005-2008 . The population used in this study is the overall manufacturing companies listed in Indonesia Stock Exchange ( IDX ) in 2005-2008 which resulted in 122 sample companies . This test uses two observation periods , namely the period of Bullish and Bearish Period , the tests used in this study is a independent simple t-test. The results of testing the hypothesis that the existence of over-reacting to events that occurred during the testing concluded that there are indications of excessive reaction ( overreaction ) are marked with the loser portfolio outperformed the winner portfolio . This overreaction effect occurs is not constant over a long time , but occur separately or separatist . This happens either in the period or periods bearish trend during the observation period